Clinical Presentation of a Patient with Congenital Cutis Laxa and Abnormal Thyroid Hormone Levels - Yan Ma; Jin-yu Zhang; Chen Wang; Wen Cen; Xin Liu; Wen-li Feng (Karger Publishers, 2014)
We describe a case of generalized cutis laxa (CL) in a 7-year-old female child. At 2 months of age, she was found to have a hoarse voice, and at 3 years, she was much smaller than her peers. Her aging face and short stature caught our attention, and the treatment of the patient was accepted by our hospital. She underwent a thorough examination. X-ray of the wrist bone showed a markedly delayed bone age, and thyroid function tests revealed significantly elevated free triiodothyronine 3 and free thyroxine 4 levels, but thyrotropin was within the normal range. Thyroid dysfunction and CL can be associated with lagged growth and development. Whether her abnormal development was due to thyroid dysfunction or CL could not be ascertained. CL is possibly more complex than it has been supposed so far, and is therefore worth to be further studied.